2019
DOI: 10.1021/jacs.9b09953
|View full text |Cite
|
Sign up to set email alerts
|

Toward Complete Resolution of DNA/Carbon Nanotube Hybrids by Aqueous Two-Phase Systems

Abstract: Sequence-dependent interactions between DNA and single-wall carbon nanotubes (SWCNTs) are shown to provide resolution for the atomic-structure-based sorting of DNA-wrapped SWCNTs. Previous studies have demonstrated that aqueous two-phase (ATP) systems are very effective for sorting DNA-wrapped SWCNTs (DNA-SWCNTs). However, most separations have been carried out with a polyethylene glycol (PEG)/polyacrylamide (PAM) ATP system, which shows severe interfacial trapping for many DNA-SWCNT dispersions, resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 96 publications
(166 reference statements)
4
58
0
Order By: Relevance
“…In the past years ATPE of SWCNTs made tremendous progress in isolation of various small and large SWCNT chiralities. 40,[44][45][46][47] In this approach SWCNTs are dispersed either in a surfactant such as deoxycholate (DOC) or chirality-specific ssDNA 48,49 sequences and separated between aqueous phases of two different polymers. This fast, reliable and low-cost separation method appears to be an optimal starting point to obtain monochiral sensors.…”
Section: Introductionmentioning
confidence: 99%
“…In the past years ATPE of SWCNTs made tremendous progress in isolation of various small and large SWCNT chiralities. 40,[44][45][46][47] In this approach SWCNTs are dispersed either in a surfactant such as deoxycholate (DOC) or chirality-specific ssDNA 48,49 sequences and separated between aqueous phases of two different polymers. This fast, reliable and low-cost separation method appears to be an optimal starting point to obtain monochiral sensors.…”
Section: Introductionmentioning
confidence: 99%
“…It has to be noted that the outcome of the separation could also be affected by varying the MW of the polymer. Lyu et al reported that by changing the MW of the employed PEG different partitioning can be obtained 51 . The impact of Pluronic MW and its composition on the course of the separation will be studied by us in the future.…”
Section: Resultsmentioning
confidence: 99%
“…We wanted to evaluate whether the ATPE system can be optimized, using high-throughput analysis, to non-ionic surfactant and DNA-SWCNT hybrids. For this experiment, we selected a TTT-CCC-TTT-CCC-CCC ssDNA super-sequence recently reported to have a high affinity towards (8,3) and a few other SWCNT types in ATPE 51 . A super-sequence, according to this work, is a sequence able to resolve more than two kinds of SWCNTs from a single DNA-SWCNT dispersion.…”
Section: Resultsmentioning
confidence: 99%
“…24,46,49 DNA-assisted sorting is another attractive option since its sequence can be engineered to enhance its interaction towards a specific type of SWCNT. 50 Similarly, various other polymers and copolymers have been designed to selectively interact with specific SWCNTs. For example, Tetronic with hydrophilic blocks favors metallic SWCNTs while Pluronic that has short hydrophobic chains shows high affinity towards semiconductor SWCNTs.…”
Section: Separation and Sortingmentioning
confidence: 99%